Traumatic Labyrinthine Concussion in a Patient with Sensorineural Hearing Loss. Issue 1 (1st February 2013) - Chiaramonte, R.; Bonfiglio, M.; D'Amore, A.; Viglianesi, A.; Cavallaro, T.; Chiaramonte, I.
Blunt head trauma without any temporal bone fracture or longitudinal temporal bone fracture, with an associated fracture of the labyrinth may cause labyrinthine injury with sensor neural hearing loss and vertigo because of a concussive injury to the membranous labyrinth. Sudden sensory neural hearing loss is relatively frequent. In most cases, the etiology is not discovered. One of the possible causes for sudden deafness is inner labyrinth bleeding or concussion, which were difficult to diagnose before the advent of magnetic resonance imaging. Vertigo without a demonstrable fracture may also be the result of labyrinthine concussion, cupololithiasis and perilymphatic fistula. We describe the clinical case of a patient with acute traumatic hearing loss and vertigo, without skull base fracture detected on computed tomography. Magnetic resonance study was also performed. We have integrated the discussion with features that allow the differential diagnosis from other similar conditions.